Effect of Marble Slurry and Recycled Aggregate in Different Grade of Concrete - Dr. Rambha Thakur, Balram (International Journal of New Media Studies: International Peer Reviewed Scholarly Indexed Journal, 2023)
In this world of rapid urbanization the demand for natural construction materials is increasing day by day which has created a necessity for alternative construction materials. The reduction in the sources of natural sand and aggregate and the requirement in the cost of concrete production has resulted in the increased need to identify substitute material to sand as fine aggregates and recycled aggregate as course aggregate in the production of concretes. Quarry dust and recycled aggregate are waste products which are released directly into the environmental and can cause environment pollution. Quarry dust a waste from the stone crushing unit accounts 25% of the final product from stone crushing unit. Recycled aggregate is a waste from demolition of concrete from buildings or structures consisting of concrete.